Analisis Sistem Penghitungan dan Pelaporan Pajak Penghasilan Pasal 21 Atas Gaji Pegawai Tetap Pada Kantor Pelayanan Perbendaharaan Negara Kolaka Utara. - Fitri Indah Sari M. (Pusat Penerbitan dan Publikasi Ilmiah FEB-UMI, 2024)
This study aims to analyze the calculation and reporting system of income tax article 21. Research Results The calculation of income tax (PPh) article 21 at the treasury service office still uses Law No. 17 of 2000 as the basis for calculation. This can be seen in terms of: PTKP, office costs, tax rates and taxable income (PKP) which still use the old rates..